JOB DEMAND DAN IMPLIKASINYA TERHADAP WORK ENGAGEMENT KARYAWAN GENERASI Z DI PT X - Kevin Adi Putra Nugraha; Sutarto Wijono (Bajang Institute, 2026)
This study aims to examine the implications of job demand on work engagement among Generation Z employees at PT X. The research employed a quantitative approach with a causal design. The participants consisted of 100 Generation Z employees selected through a random purposive sampling technique. Data were collected using the Job Demand Scale adapted from the Job Demands-Resources Questionnaire and the Work Engagement Scale adapted from the Utrecht Work Engagement Scale (UWES-17). Data analysis was conducted using descriptive statistics, normality tests, linearity tests, Pearson correlation, and simple linear regression with the assistance of Jamovi software. The findings revealed that both job demand and work engagement were at a moderate level. Pearson correlation analysis indicated a positive and significant relationship between job demand and work engagement (r = 0.298; p < 0.003). Furthermore, simple linear regression analysis showed that job demand had a positive and significant effect on work engagement with a regression coefficient of 0.285 (t = 3.09; p = 0.003) and a coefficient of determination (R²) of 0.088. These results indicate that job demand contributes 8.8% to work engagement. The findings suggest that job demands perceived as challenges can enhance employees’ vigor, dedication, and involvement in their work. However, the relatively small contribution implies that other factors, such as job resources, psychological capital, organizational support, and work-life balance, may play a more dominant role in influencing work engagement among Generation Z employees